Effects of a phase change cooling garment during exercise in the heat - Butts, C. L.; Torretta, M. L.; Smith, C. R.; Petway, A. J.; McDermott, B. P. (European Journal of Sport Science, 2017)
The purpose of our study was to examine the physiological, perceptual, and performance effects of wearing a phase change cooling garment (CG) during an interval exercise routine in the heat. Sixteen male participants (age 23 ± 3 years, ht 1.76 ± 0.11 m; wt 78.5 ± 11.2 kg; body fat 15.2 ± 5.8%) completed two trials (one with phase change inserts, CG, and one control without inserts) consisting of two submaximal exercise portions separated by 5-minute seated rest, and a final maximal effort performance bout. Each submaximal bout involved 30 seconds or 1 minute of muscular endurance and agility exercises and 5 minutes of treadmill jogging and step-ups. The performance bout included 30 seconds or 1 minute of muscular endurance and agility exercises, with participants completing as many repetitions as possible, followed by a 15-minute recovery (active and passive). Rectal temperature (Tre) and heart rate were not different between trials, however change in Tre from baseline was improved during 10 and 15 minutes of recovery with the CG (P < .05). Mean skin temperature was lower using the CG vs control throughout the trial (P < .05). Thermal sensation was lower when using the CG compared to control (P < .001). There were no differences in any outcomes of the performance exercises (P > .05). These findings indicate that the continuous use of a CG during an interval style workout in the heat provides improvements in thermal sensation, however, only minimal thermophysiological benefits, and no performance augmentation.